Mechanical Characterization of Biocomposites Reinforced with Untreated and 4% NaOH-Treated Sisal and Jute Fibres - D. P. Archana; H. N. Jagannatha Reddy; Basavaraju Paruti (Advances in Materials Science and Engineering)
Composites reinforced with natural fibres have gained popularity compared to synthetic fibre-reinforced polymer composites due to their environmental sustainability, despite their reduced stiffness and load-bearing capability. In this work, the biocomposites reinforced with sisal and jute fibres which are made by hand layup technique were investigated for mechanical and water absorption characteristics. The effect of a 4 percent NaoH treatment concentration on the aforementioned properties was investigated. The specimens’ tensile and flexural broken surfaces were morphologically characterized to investigate microstructural failures. The experimental results show that, compared to untreated fibre-reinforced composites, the biocomposites reinforced with 4 percent NaoH-treated fibre exhibit higher tensile, flexural, and impact strengths, as well reduced water absorption rate. These composites are aimed to be used for strengthening existing civil structures as a retrofitting element.